Iron Oxide Supported on Al2O3 Catalyst for Methane Decomposition Reaction: Effect of MgO Additive and Calcination Temperature. Issue 2 (26th January 2016) - Al‐Fatesh, Ahmed S.; Fakeeha, Anis H.; Ibrahim, Ahmed A.; Khan, Wasim U.; Atia, H.; Eckelt, R.; Chowdhury, Biswajit
Abstract: Production of hydrogen is a challenging task and have significant impact in the recent scenario. The alumina supported iron oxide nanoparticle synthesized using non‐ionic surfactant Triton‐X was found very effective for steady production of hydrogen through methane decomposition reaction. The high surface area, easily reducible catalyst calcined at 500 °C and 800 °C temperature showed steady activity towards methane decomposition reaction. At a higher reaction temperature there was catalyst deactivation. The doping of MgO facilitated particle growth rendering the poor catalytic activity. The TPR study showed that reducibility of TPR was difficult in presence of MgO additive. The formation of FeMgAl solid solution confirmed by XRD study was found mainly responsible for the lower catalytic activity. The bamboo‐shaped carbon nanotube formed from 20 % Fe/Al2 O3 catalyst which is mainly because of the poor wetting property of quasi‐liquid metal and carbon nanotube. Abstract : Hydrogen is a promising energy carrier. The catalytic performance results for MgO doped Fe/Al2 O3 catalysts, calcined at different temperatures, for CH4 decomposition showed that catalyst calcined at 400 °C exhibited better activity as compared to other catalysts. Moreover, Fe/Al2 O3 catalyst revealed the formation of multi‐walled nanotubes as evidenced by TEM.